Use and competition at artificial feeding sites : the roe deer and fallow deer case - Cederholm, Tina (SLU/Dept. of Ecology, 2012)
Fallow deer is an exotic species in Sweden; it was brought here in the 1570s and has now established viable, wild populations in the southern parts of Sweden. Roe deer is native in Sweden and there is a concern that it is displaced by fallow deer in areas where both species exists, as reported from other countries. The aim of this study was to investigate if there is an effect of competition at artificial feeding sites by fallow deer on roe deer, more specific, to measure the use of feeding sites at different month and type of winters. In addition, by divide individuals into age classes and sex, also get a more precise measure of feeding site use. The data for this study consisted of GPS-positions from 31 roe deer and 50 fallow deer during six winter seasons (2006-2012). An individual within 50m of the feeding station was counted as utilizing the feeding site. Both roe deer and fallow deer increased feeding site use during a hard winter and decreased their use in a mild winter. Fallow deer males used feeding sites more than roe deer and fallow deer females. The two species did use the feeding sites differently each month. Fallow deer used feeding sites more than roe deer in all months except for February and March. However, the high use by roe deer in February and March were driven by 6 females and 1 male. The feeding site use was not different among different age classes in roe deer. There was a trend that older fallow deer males use feeding sites more than younger males. Fallow deer females always used feeding sites less than fallow deer males. Fallow deer males had three feeding activity peaks during a day and a long pause between each. Fallow deer females on the other hand, did have a daily pattern that is more similar to the roe deer. This study conclude that fallow deer used feeding sites more than roe deer, but it did not detect any clear evidence of competition between the two species. However, the low use by fallow deer females could be an indication of intra-specific competition.